Harmonizing famous trademark protection: brand dilution and recognition under trips and the madrid protocol - Yusuf Gunawan; Gatot Subroto Widagdo; Vidi Galenso (Lentera Negeri, 2026)
This article examines whether the interaction between the TRIPS Agreement and the Madrid Protocol provides coherent international protection for well-known marks against dilution. The study uses normative doctrinal research and comparative document analysis. The corpus comprises six primary instruments and guidance texts - the Paris Convention, the TRIPS Agreement, the Madrid Protocol, the Regulations under the Protocol, the WIPO Joint Recommendation on Well-Known Marks, and the WIPO Madrid Guide - together with fifteen scholarly sources selected from official, publisher, and institutional repositories. Documents were coded according to legal status, fame threshold, scope of protection, treatment of dissimilar goods and services, procedural effect, and enforcement consequence. The analysis finds that TRIPS Article 16(3) establishes a minimum substantive extension for registered well-known marks where use on dissimilar goods or services indicates a connection and is likely to damage the owner's interests, but it does not define blurring, tarnishment, evidentiary thresholds, or remedies. The Madrid Protocol centralizes filing and administration while preserving national examination, refusal, and enforcement; therefore, international registration does not create a unitary substantive right. The WIPO Joint Recommendation supplies more detailed recognition and anti-dilution factors, but it remains non-binding. The principal gap is thus the absence of operational alignment between substantive standards and the administrative registration system. The article proposes a four-part alignment framework: common fame factors, an express and balanced dilution ground, reasoned and interoperable national decisions, and coordinated WTO-WIPO guidance with capacity support. The findings are doctrinal and do not claim uniform national implementation.